Adaptation of the Ukrainian Version of Autonomous Career Motivation Scale - Lytvynenko, Olena; Korkos, Yaroslav (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2025)
The paper aims to present the results of adaptation of the Ukrainian version of Autonomous Career Motivation Scale (Sverko & Babarović, 2024). Methods. At the preparatory stage of adaptation the double translation procedure was carried out for the Ukrainian version of the scale to correspond as closely as possible to the original one. After that, the equivalence between the original scale and its translated version was assessed. The study sample (N=336) included: 1) high school students (14-17 y. o.) – 68.15%; 2) first year university students (17-20 y. o.) – 31.85%. The gender distribution of respondents was following: 1) female – 65.18%; 2) male – 30.36%; 3) unidentified – 4.46%. Results. The results of the study confirm theoretical structure of the Scale, which is consistent with previous conceptual ideas about the measurement construct. Exploratory factor analysis allowed us to identify a clear factor structure that supports the hypotheses about the multidimensionality of the concept and indicates the sociocultural stability of the model. Conformational factor analysis showed high indicators of model compliance, which proves the adequacy of the chosen structure, however, some accuracy indicators demonstrate potential for further improvement of the model. The reliability of the scales is at an acceptable and high level, wh0ich confirms their consistency, homogeneity and ability to stably reflect the measured construct. Convergent and discriminant validity of the Scale are also confirmed, which demonstrates the ability of the Scales to correlate with the corresponding items and at the same time distinguish between different constructs. The high discriminantity of the scales indicates the effectiveness of the tool in distinguishing different aspects of career motivation, which is important for further use of the questionnaire in empirical research and for achieving practical goals by psychologists, career counsellors, etc. Conclusions. The Ukrainian version of Autonomous Career Motivation Scale shows a number of high psychometric indicators, which allow to positively assess the factor structure (model), reliability, construct, convergent and discriminant validity and discriminantity of its subscales. Obtained results indicate the effectiveness of using this Scale to measure autonomous career motivation, while indicating directions for further optimization of the model.